Measuring the Full Extent of Fiscal Losses and Gains - Coulibaly, Mohamed; Sanoh, Aly (World Bank, Washington, DC, 2019)
Current measures of fiscal impoverishment and gains are not consistent with the law of diminishing returns. This paper proposes new measures of fiscal impoverishment and gains that are consistent with the law of diminishing returns, based on a methodology that gives more significance to greater income gaps, and more importance to the experience of the poorest individuals within the fiscal system. The new indicators are decomposable and cover the incidence, intensity, and severity of fiscal impoverishment and gains. An empirical illustration using the 2014 household consumption data reveals that, overall, in Niger the fiscal system is improving the welfare of the population: only 33.2 percent of the population has become poorer due to the fiscal system, while the remaining 66.8 percent has become richer because of it. Moreover, the mean relative fiscal loss (0.014), is 11 percent lower than the mean relative fiscal gain (0.126).